2020
DOI: 10.2967/jnumed.119.240143
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-DOTATATE PET/CT and Prediction of Overall and Progression-Free Survival in Patients with Neuroendocrine Neoplasms

Abstract: Overexpression of somatostatin receptors in patients with neuroendocrine neoplasms (NEN) is utilized for both diagnosis and treatment. Receptor density may reflect tumor differentiation and thus be associated with prognosis. Non-invasive visualization and quantification of somatostatin receptor density is possible by somatostatin receptor imaging (SRI) using positron emission tomography (PET). Recently, we introduced 64 Cu-DOTATATE for SRI and we hypothesized that uptake of this tracer could be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…To evaluate the benefits of this better detection of lesions with [ 64 Cu]-DOTATATE than with [ 68 Ga]-DOTATOC, the correlation between PET image [ 64 Cu]-DOTATATE uptake (expressed in maximal standardized uptake value - SUV max ) and overall (OS)/progression free survival (PFS) was studied during 24 months after [ 64 Cu]-DOTATATE PET/CT acquisition. The conclusion of this study claimed a good correlation/prognostic between SUV max and PFS but not with OS [ 121 ]. The major drawback of these preliminary human studies consist of the affinities differences for the five SSTRs subtypes between DOTATOC and DOTATATE compounds.…”
Section: Targeting Of Somatostatin Receptors With Radiopharmaceutimentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the benefits of this better detection of lesions with [ 64 Cu]-DOTATATE than with [ 68 Ga]-DOTATOC, the correlation between PET image [ 64 Cu]-DOTATATE uptake (expressed in maximal standardized uptake value - SUV max ) and overall (OS)/progression free survival (PFS) was studied during 24 months after [ 64 Cu]-DOTATATE PET/CT acquisition. The conclusion of this study claimed a good correlation/prognostic between SUV max and PFS but not with OS [ 121 ]. The major drawback of these preliminary human studies consist of the affinities differences for the five SSTRs subtypes between DOTATOC and DOTATATE compounds.…”
Section: Targeting Of Somatostatin Receptors With Radiopharmaceutimentioning
confidence: 99%
“…Compared to 68 Ga, in addition to economic advantages, 64 Cu has a lower positron range which leads to a better PET intrinsic resolution and a higher half-life which allows for a more flexible scanning window. The better patient care management and outcomes remain to be proven and the work is in progress to establish these points [ 121 , 125 ]. In parallel, at present, a radiopharmaceutical industrial company submitted a market authorization from FDA for [ 64 Cu]-DOTATATE and thus confirms the interest of copper-64 in SSTRs imaging.…”
Section: Targeting Of Somatostatin Receptors With Radiopharmaceutimentioning
confidence: 99%
“…In several studies, SSTR imaging was shown not only to correlate with the gene expression of SSTR in NETs but also with the Ki-67-index, and it was found to be an important predictive factor for survival [ 23 , 24 , 25 , 26 , 27 ]. Furthermore, the molecular imaging of NETs has a major impact on treatment planning [ 28 ].…”
Section: Imaging and Therapy Of Sstr-positive Netsmentioning
confidence: 99%
“…Recent data show that SSTR-PET/CT with Copper-64 with a SUVmax cutoff of 43.3 could predict PFS after 24 months of follow-up with a moderate accuracy of 57%. However, a matched comparison with the predictive value of Gallium-68-labelled imaging in the same population was missing in the study [ 26 ].…”
Section: Imaging and Therapy Of Sstr-positive Netsmentioning
confidence: 99%
“…Compared with other SSTR-based PET radiopharmaceuticals, 64 Cu-DOTATATE has the advantage of a flexible acquisition time window ranging from 1 to 3 h after injection with the same lesion detection ability [ 15 ]. Recently, we showed that lesion standardized uptake values (SUV max ) derived from 64 Cu-DOTATATE PET/CT provided prognostic information on progression-free survival for patients with NENs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%